Homozygosity for a missense mutation in the 67 kDa isoform of glutamate decarboxylase in a family with autosomal recessive spastic cerebral palsy: parallels with Stiff-Person Syndrome and other movement disorders - Woods C Geoffrey; Maher Eamonn R; Mitchell Simon; Achuthan Rajgopal; Leek Jack P; Carr Ian M; Lynex Clare N; Bonthon David T; Markham Alex F (BMC Neurology, 2004)
Abstract Background Cerebral palsy (CP) is an heterogeneous group of neurological disorders of movement and/or posture, with an estimated incidence of 1 in 1000 live births. Non-progressive forms of symmetrical, spastic CP have been identified, which show a Mendelian autosomal recessive pattern of inheritance. We recently described the mapping of a recessive spastic CP locus to a 5 cM chromosomal region located at 2q24-31.1, in rare consanguineous families. Methods Here we present data that refine this locus to a 0.5 cM region, flanked by the microsatellite markers D2S2345 and D2S326. The minimal region contains the candidate gene GAD1, which encodes a glutamate decarboxylase isoform (GAD67), involved in conversion of the amino acid and excitatory neurotransmitter glutamate to the inhibitory neurotransmitter γ-aminobutyric acid (GABA). Results A novel amino acid mis-sense mutation in GAD67 was detected, which segregated with CP in affected individuals. Conclusions This result is interesting because auto-antibodies to GAD67 and the more widely studied GAD65 homologue encoded by the GAD2 gene, are described in patients with Stiff-Person Syndrome (SPS), epilepsy, cerebellar ataxia and Batten disease. Further investigation seems merited of the possibility that variation in the GAD1 sequence, potentially affecting glutamate/GABA ratios, may underlie this form of spastic CP, given the presence of anti-GAD antibodies in SPS and the recognised excitotoxicity of glutamate in various contexts. <tbl id="T4"> Table 4 GAD1 single nucleotide substitutions detected on mutation analysis and occurring in sequences submitted to NCBI SNP database and in the literature. This is not a definitive list, but includes those described at the time of the mutational analysis. *Nucleotide positions were not provided by Maestrini et al. [47]. <tblbdy cols="4"> <r> <c ca="center"> Source </c> <c ca="center"> SNP position in mRNA, from the translational start site (bp) </c> <c ca="center"> Gene position of SNP(bp) </c> <c ca="center"> Amino acid change </c> </r> <r> <c cspan="4"> </c> </r> <r> <c ca="center"> (A)Lappalainen et al. (2002) </c> <c ca="center"> A(-478)Del </c> <c ca="center"> Exon 0 (73) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (B)Lappalainen et al. (2002) </c> <c ca="center"> G(-147)A </c> <c ca="center"> Exon 0 (404) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (C)Lappalainen et al. (2002) </c> <c ca="center"> A(-39)C </c> <c ca="center"> Exon 1 (25) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (D)Spastic CP patients family B </c> <c ca="center"> G(36)C </c> <c ca="center"> Exon 1 (97) </c> <c ca="center"> Ser(12)Cys </c> </r> <r> <c ca="center"> (E)NCBI collated resource </c> <c ca="center"> G(48)C </c> <c ca="center"> Exon 1 (104) </c> <c ca="center"> Pro(17)Ala </c> </r> <r> <c ca="center"> (F)Control samples & family A NCBI collated resource </c> <c ca="center"> T(110)C </c> <c ca="center"> Exon 2 (29) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (G)Kure et al. (1998) </c> <c ca="center"> T(315)C </c> <c ca="center"> Exon 4 (14) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (H)Bu and Tobin (1994) Kure et al. (1998) </c> <c ca="center"> A(407)G </c> <c ca="center"> Exon 4 (105) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (I)Maestrini et al. (2002)* </c> <c ca="center"> G/C </c> <c ca="center"> Intron 4 </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (J)NCBI collated resource </c> <c ca="center"> C(696)T </c> <c ca="center"> Exon 6 (56) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (K)Lappalainen et al. (2002) </c> <c ca="center"> T/Del </c> <c ca="center"> Intron 7 (35) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (L)In control samples Lappalainen et al. (2002) </c> <c ca="center"> T/C </c> <c ca="center"> Intron 8 (185) </c> <c ca="center"> No substitution </c> </r> <r> <c ca="center"> (M)Maestrini et al. (2002)* </c> <c ca="center"> C/T </c> <c ca="center"> Intron 9 </c> <c ca="center"> No substitution </c> </r> </tblbdy> </tbl>